New Insights into rice pyrimidine catabolic enzymes - Lopez, Andrea J.; Narvaez-Ortiz, Heidy Y.; Rincon-Benavides, Maria A.; Pulido, Dania Camila; Fuentes Suarez, Luis Eduardo; Zimmermann, Barbara H. (Frontiers in Plant Science, 2023)
Rice is a primary global food source, and its production is affected by abiotic stress, caused by climate change and other factors. Recently, the pyrimidine reductive catabolic pathway, catalyzed by dihydropyrimidine dehydrogenase (DHPD), dihydropyrimidinase (DHP) and β-ureidopropionase (β-UP), has emerged as a potential participant in the abiotic stress response of rice. The three enzymes from rice were produced as recombinant proteins, and two were kinetically characterized. The rice dihydroorotate dehydrogenase (DHODH), an enzyme of the de novo pyrimidine biosynthetic pathway often confused with DHPD, was also expressed and characterized. Alignments showed that the 413-residue rice DHPD was homologous to the C-terminal half of the mammalian DHPD, conserving the FMN and uracil binding site residues. The plant enzyme lacked binding sites for Fe/S clusters, FAD, and for the reductant NADPH. A recombinant version of OsDHPD, truncated to eliminate the chloroplast targeting peptide, was soluble, but inactive. Database searches for independent polypeptides homologous to the N-terminal half of mammalian DHPD, that could act as co-reductant partner proteins, were unsuccessful. Recombinant OsDHODH exhibited kinetic parameters that were similar to those of other plant DHODHs. Recombinant OsDHP, truncated to remove the endoplasmic reticulum targeting peptide, exhibited a specificity constant of 3.6 x 103 s-1M-1, and is the first such enzyme from plants to be characterized. Recombinant Osβ-UP had a specificity constant of 1.8 x 104 s-1M-1, in the range of enzymes of secondary metabolism. Salt-sensitive and salt-resistant rice seedlings subjected to short salt stress (24 h) showed insignificant changes in levels of the pathway intermediates dihydrouracil and ureidopropionic acid, which are both ureide compounds. Allantoin, a ureide metabolite of purine catabolism, thought to scavenge reactive oxygen species, was found to be significantly higher in the resistant cultivar compared to one of the sensitive cultivars.